A procedure for reducing stock–keeping unit variety by linking internal and external product variety. (May 2022) - Staśkiewicz, Aleksandra Magdalena; Hvam, Lars; Haug, Anders
Abstract: While the literature has paid significant attention to product variety management, only sparse consideration has been given to its relationship with supply chain processes. To address this gap in the literature, this paper describes a procedure for stock–keeping unit (SKU) reduction that provides a transparent link between internal variety (component and module level) and external variety (finished goods level) and relates this to supply chain processes. When applied at a large international company that manufactures hearing aids, the procedure achieved a 33% reduction in SKU variants at the module/component level while maintaining the end–product variety offered to customers.